Students' Competence in Understanding Adab Material: A Correlational Study of Their Independent Attitudes - Mochammad Ichsan Wardana; Muhammad Raffi Firdaus; Dea Asmara; Nadiya Dzill Izzat; Muhammad Hilba Azmuna; Deksa Ira Lindriyati; Listiyani Siti Romlah (Action Research Journal Indonesia (ARJI), 2025)
The primary focus of this research lies in the limited mastery of ethical values (adab) among students, which hampers the development of self-reliant attitudes. As a core component of character education, adab plays a critical role in cultivating responsibility, independence, and moral awareness. This study aims to analyse the relationship between self-awareness levels, including independent attitudes, and cognitive learning outcomes (comprehension level, C2) among eighth-grade students at MTs Daarul Ma'arif, South Lampung. A quantitative correlational approach with an ex-post facto design was employed, involving 59 participants selected through simple random sampling from a total population of 144 students. Research instruments included a validated five-point Likert-scale questionnaire and a cognitive achievement test. Normality tests (Kolmogorov-Smirnov and Shapiro-Wilk) indicated non-normal data distribution (significance < 0.05), necessitating non-parametric statistical analysis. The primary analytical methods comprised Spearman correlation to assess variable relationships, alongside linearity and coefficient of determination tests to evaluate the form and strength of associations. Results revealed a statistically significant negative correlation between self-reliance and adab comprehension, suggesting that misdirected independence may undermine the internalisation of ethical values. These findings underscore the importance of balanced instructional strategies that integrate self-directed learning with guided social interaction. The study's implications highlight the need for educators and policymakers to develop contextual and reflective character-education models. Recommendations include reinforcing adab comprehension through collaborative approaches, role modelling, value-based habituation, and addressing factors such as intrinsic motivation, family support, and teacher-student communication patterns.